Roles of extracellular vesicles in the aging microenvironment and age‐related diseases - Yin, Yujia; Chen, Huihui; Wang, Yizhi; Zhang, Ludi; Wang, Xipeng (Journal of extracellular vesicles, 2021)
Cellular senescence is a persistently hypoproliferative state with diverse stressors in a specific aging microenvironment. Senescent cells have a double‐edged sword effect: they can be physiologically beneficial for tissue repair, organ growth, and body homeostasis, and they can be pathologically harmful in age‐related diseases. Among the hallmarks of senescence, the SASP, especially SASP‐related extracellular vesicle (EV) signalling, plays the leading role in aging transmission via paracrine and endocrine mechanisms. EVs are successful in intercellular and interorgan communication in the aging microenvironment and age‐related diseases. They have detrimental effects on downstream targets at the levels of immunity, inflammation, gene expression, and metabolism. Furthermore, EVs obtained from different donors are also promising materials and tools for antiaging treatments and are used for regeneration and rejuvenation in cell‐free systems. Here, we describe the characteristics of cellular senescence and the aging microenvironment, concentrating on the production and function of EVs in age‐related diseases, and provide new ideas for antiaging therapy with EVs.